The identification and genetic characteristics of the Orf virus strain (ORFV-CL24) isolated from Jilin province, China - Lv, Lijun; Gao, Fei; Guan, Jiyu; Sun, Yiran; Zhang, Ran; Li, Zi; Lan, Yungang; Gao, Feng; He, Wenqi; Zhao, Kui (Frontiers in Microbiology, 2025)
Orf virus (ORFV), the prototype species of the Parapoxvirus genus within the Poxviridae family (subfamily Chordopoxvirinae), is a global pathogen infecting sheep, goats, and other ruminants, with zoonotic potential for humans. In this study, an outbreak of ORFV infection occurred in a sheep flock in Changling County, Jilin province, China, causing papules, pustules, and crusting lesions on the lips and eyelids. Typical parapoxvirus particles were observed using electron microscopy, and a wild ORFV strain was isolated, characterized, and designated as ORFV-CL24. To clarify the epidemiological and genomic characteristics of ORFV in the region, we completed its whole-genome sequencing (GenBank accession number: PV126639). Genome analysis revealed that ORFV-CL24 shares a conserved structure with other isolates available in GenBank, which possess a complete genomic sequence of 138,500 bp of dsDNA harboring 131 putative open reading frames (ORFs) flanked by inverted terminal repeat (ITR) regions of 3,264 bp at both termini. Additionally, the genome exhibited high GC-content (63.3%), indicating its key role in DNA stability. Phylogenetic analysis placed the wild strain within a subclade with the attenuated ORFV strain D1701, implying a putative common ancestor or epidemiological linkages. Further analysis of B2L (ORFV 011) and E3L (ORFV 020) genes further revealed genetic diversity and evolutionary patterns. Notably, despite phylogenetic relatedness, specific mutations in ORF020 further distinguished ORFV-CL24 from D1701, reflecting stepwise mutation accumulation during host adaptation. In conclusion, our results provided valuable genetic insights into ORFV-CL24, which contributed to a better understanding of its evolution, biological properties, and endemic trends in China.